Evaluation of Trainers' Training programme on Scaling up of Water Productivity in Agriculture - Meena, B.S.; Yadav , B.S. (Indian Journal of Extension Education, 2013)
The study was an attempt to evaluate the impact of 14 days trainers' training programme on judicious use of irrigation  water in agriculture and horticultural crops under the project "Scaling up of water productivity in agriculture for  livelihood through teaching cum demonstration" sponsored by Ministry of Agriculture, Government of India and was  organized by Agricultural Research Station, Sriganganagar from 14.09.2011 to 27.09.2011. It was attended by 26 male  participants consisting of extension personnel and subject matter specialists with the objective to create trained manpower  for efficient use of limited irrigation water in agricultural and horticultural crops. A well structured interview scheduled  was developed and used. The study revealed that majority of the trainees was above 40 years of age having 10 to 20 years  of service experience. After undergoing this training, there was a knowledge gain of 44.23 per cent. The trainees perceived  the topics related to crop and water management as highly relevant (80 %). Overall, 63.30 per cent of the topics were  perceived as highly relevant by the trainees followed by 27.1 per cent topics which were perceived as quite relevant and  useful. All the trainees (100 %) agreed that their knowledge had increased .The level of increased was varied. They opined  that during the training the learning environment was excellent and reported that their confidence level has increased  (78%) and satisfied with the duration of the training. More than half (58%) of the trainees agreed that they have developed  new skills by attending the training. Overall, 82.8 per cent of the trainees were agreed on various aspects of training  programme followed by 11.1 per cent which were neutral and 6.1 per cent were disagreed with the organization of the  training programme.
Keywords: Training; water management; knowledge; aspects of training